2009
DOI: 10.1080/02652030902896194
|View full text |Cite
|
Sign up to set email alerts
|

Antimutagenic and antigenotoxic effects of vegetable matrices on the activity of pesticides

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, some controversial data exist regarding fludioxonil and cyprodinil. The Ames mutagenicity data reported by EFSA for these two fungicides gave negative results, whereas more recently, Isidory and coworkers [Isidori et al, 2009] reported that these compounds were shown to be poten-tially mutagenic with both the Ames assay and the SOS chromotest. Moreover, in vitro chromosomal aberration was observed with fludioxonil on CHO cells as well as unscheduled DNA synthesis in primary rat hepatocytes [EFSA, 2007].…”
Section: Discussionmentioning
confidence: 97%
“…However, some controversial data exist regarding fludioxonil and cyprodinil. The Ames mutagenicity data reported by EFSA for these two fungicides gave negative results, whereas more recently, Isidory and coworkers [Isidori et al, 2009] reported that these compounds were shown to be poten-tially mutagenic with both the Ames assay and the SOS chromotest. Moreover, in vitro chromosomal aberration was observed with fludioxonil on CHO cells as well as unscheduled DNA synthesis in primary rat hepatocytes [EFSA, 2007].…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, the populations studied in this work come from a rural area, where a great amount of vegetables and fruit are consumed. Isidori et al (2009) reported the antimutagenic and antigenotoxic effects of vegetables on the activity of several pesticides using the Ames test. Thus, we could hypothesize that substances present in this kind of diet might have exerted a protective effect against pesticide exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, co-incubation of phenolic extract from Fresh bean and aflatoxin B1 was reported to significantly reduce the mutagenicity and thus the possibility of chemical complex formation was proposed as a mechanism [141]. Antimutagenic effects of vegetable matrices on the activity of pesticides were observed in Ames test and SOS Chromotest [144]. In that study, the antimutagenicity of vegetables was proposed to be related to the antioxidant activity.…”
Section: Gautam Et Almentioning
confidence: 98%